THE IMPACT OF DRIVER’S BEHAVIOR IN ROAD TRAFFIC ACCIDENT (International Journal of Food and Nutritional Sciences, 2022)
In India, with reference to Urban roads, the task of ensuring safe traffic is difficult due to the combination of slow and fast moving vehicles, sharing the same carriage way. In general, accidents are found to be due to carelessness, thoughtlessness, over confidence and not due to ignorance. Various factors like human, vehicle and environment factors play a major roles in road traffic accident (Haddon, 1974). In India scenario of mixed traffic comprising bicycles, tricycles, animal-drawn carts, and motor vehicles of various sizes, shapes and speeds, without adopting traffic segregation measures are found. WHO 2018 reports has revealed the fact that India had only 1% of world’s motor vehicle population but accounts for 6% of road accidents. In 2018, India reported 73% of total deaths which occurred due to road accidents in entire south Asian region. Further, Road accidents were found to be the ninth most common cause for premature deaths and tenth most common cause for disability. There are various reasons which contributed towards road traffic accidents. Among different factors, human factors plays a significant role which includes drunken drivers, usage of mobile phone, distraction and not following traffic laws. This paper will focus on the behavioural issues in road traffic accidents in Chennai.